Problems of Investment Planning in Upstream companies - L. R. Artemkina (Управленческие науки)
Introduction, Purpose. The upstream companies should give special consideration to the quality of the investment planning in existent conditions of high oil prices’ volatility and unstable economic situation. The goal of research is to study the current problems of investment planning in Russian upstream companies, which are caused by imperfection of the current methodology of the functional business process “Investment planning”, and to develop the recommendations on solving these problems. Methods. The general scientific research methods are used in the study: analysis and synthesis, induction, modeling and system approach. The sources of the mass media and regulatory documents of some Russian upstream companies were considered while studying the investment planning problems. Results. Three key problems of the existing approach to the investment planning in upstream companies have been identified. The first problem is the absence of regulated economic efficiency assessment of individual work packages within the framework of a general field development project (for example, sidetracking, drilling of a bush of wells, etc.). It creates the risk of inefficient investing in exploration. The second problem is the absence of an effective system of impoundment control. That leads to the overrun of investment costs plan. According to the author, the third problem of the existing methodology of investment planning is the absence of a mechanism for optimizing the company’s investment portfolio. In order to solve these problems the author proposes to implement the elements of project and portfolio management into the methodology of the functional business process “Investment planning”. That is, to use the project at the oil field as an investment planning object, to apply the phase process of large project execution, and to create a mechanism of portfolio optimization based on mathematical optimization model. Discussion. Corporate governance and investment planning specialists as well as the institutions involved in the implementation of the project management methodology can use the results of this research in their further work.